Dorongan Mencari Sensasi dan Perilaku Pengambilan Resiko pada Mahasiswa - Ratna Syifa’a Rachmahana (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2002)
This research aimed at finding correlation between sensation seeking and risk taking behavior among students. This study was done by experimental method. It was hypothesis that was a positive correlation between level of sensation seeking and risk taking behavior.Data were collected from 79 students in faculty of Psychology from Islamic University of Indonesia. The students participated in ring toses experiment, adapted from Sorrentino (1992). Before experiment, students had completed sensation seeking scale. The relationship between level of sensation seeking and risk taking behavior was determined by product moment analysis. The result of the reseach was that sensation seeking correlated with risk taking behavior (r=0,226: p= 0,045)Key Words : Sensation Seeking, Risk taking Behavior